Design, development and characterisation of a building integrated photovoltaic smart window system for electricity generation and adaptive daylighting control - Liu, Xiao (2021)
Global concerns over climate change and ever-increasing energy demand have led to a growing interest in developing renewable energy technologies. Building Integrated Photovoltaic (BIPV) window, which is conventionally designed by incorporating a semi-transparent thin film solar cell or evenly spaced crystalline-silicon (c-Si) solar cells between two layers of glass, is a promising technology to generate electricity and reduce cooling demands in buildings. In this thesis, an innovative BIPV smart window system where an optically switchable thermotropic membrane is laminated with a c-Si solar cell layer and glass covers has been proposed. The thermotropic membrane layer can switch between a transparent and light-scattering state as its temperature changes; in the meanwhile, a proportion of the scattered solar radiation is trapped in the window and redirected onto the solar cell surfaces for electricity generation. Compared with conventional BIPV windows, this smart window has the potential to offer better control of the daylight transmitted into building spaces as well as higher electrical power outputs. The concept is new, and findings regarding the window performance have not been reported in the literature. To prove this concept, in this thesis, a comprehensive research including prototype design, development and characterisations has been carried out: